CT advantages of potential use of polymer plastic clips in neurocranium - Samir Delibegović; Mirela Delibegović; Muhamed Katica; Muamer Obhodžaš; Muhamed Ođuz (Medicinski glasnik, 2022)
Aim: Clips in neurosurgery are made of titanium alloys, which reduce artifacts on computed tomography (CT). The radiological advantage of plastic clips on the CT image was demonstrated when they were placed in an inter-hemispherical position at an angle of 90º. The aim of this study was to investigate the behaviour of the clip placed at different angles. Methods: Sixty heads of domestic pigs were divided into two groups, in group 1 a titanium clip was placed to the interhemispheric position at an angle of 90º, 45º, 0º, ten heads for each angle. In group 2 a plastic clip was placed in the same way. CT scan of the brain was performed for each angle. The size of the density and possible artifact were measured on CT. Results: The size of the titanium clip ranged from 17.05 mm at an angle of 0º in the axial plane to 91.47 mm at an angle of 0º in the sagittal plane. The average size of the plastic clip ranged from 6.4 mm at an angle of 0º in the axial plane to 23.22 mm in an angle of 90º in the sagittal plane. Artifacts were observed only in the titanium clip. Conclusion: Plastic clips have shown radiological advantages over titanium clips in the CT image. The average density size of the plastic clip in all planes and all angles was smaller than the titanium clip.
Keywords: aneurysm clipping; artifacts; computed tomography